2023
DOI: 10.1002/lpor.202301027
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐Site Passivation for Bright and Stable Blue‐emitting CsPbBr3 Nanoplatelets

Rui Yun,
Wenda Sun,
Haolin Lu
et al.

Abstract: Blue‐emitting perovskite nanocrystals (NCs) are important components of high‐definition display device, but their instability to light and moisture severely hinders the commercial application. Here, a dual‐site passivation strategy is proposed and the halogen–halogen bond to surface capping molecules is applied. The bi‐functional molecule with a fluorine group and carboxyl group on the phenyl ring, would form a shell‐like molecular structure covering the nanocrystal surface at halogen and lead site via halogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Generally, blue emission can be achieved by modulating the quasi-two-dimensional (quasi-2D) quantum well distribution, enhancing the quantum confinement effect of CsPbBr 3 , or doping Cl species to change the degree of orbital overlap, respectively. 11–20 In recent years, there has been a significant focus on developing blue PeLEDs based on the first two techniques. However, it is reported that low-dimensional perovskites exhibit inefficient energy transfer, spectral broadening and even multi-peak emission owing to their complicated phase distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, blue emission can be achieved by modulating the quasi-two-dimensional (quasi-2D) quantum well distribution, enhancing the quantum confinement effect of CsPbBr 3 , or doping Cl species to change the degree of orbital overlap, respectively. 11–20 In recent years, there has been a significant focus on developing blue PeLEDs based on the first two techniques. However, it is reported that low-dimensional perovskites exhibit inefficient energy transfer, spectral broadening and even multi-peak emission owing to their complicated phase distribution.…”
Section: Introductionmentioning
confidence: 99%